Development of Android-Based Informatics Learning Media to Improve Computational Thinking in High School Students - Nurhaliza, Jihan; Hikmawan, Rizki; Arrumaisha , Nissa (Jurnal Paedagogy, 2026)
This study aims to develop an Android-based informatics learning medium, named THINQING, to enhance senior high school students’ computational thinking (CT) skills through Bebras informatics problems. The research employed a Research and Development (R&D) method using the Game Development Life Cycle (GDLC) framework, which consists of the stages of initiation, pre-production, production, testing, beta, and release. The participants of this study were 30 tenth-grade students from a senior high school in Garut Regency. Data were collected using the Computational Thinking Scale (CTS), which measures five dimensions of CT: creativity, algorithmic thinking, cooperativity, critical thinking, and problem-solving skills. Data were analyzed using a one-sample t-test by comparing students’ CTS scores with a neutral benchmark value. The results reveal a statistically significant improvement in students’ computational thinking skills, as indicated by a significance value of p < 0.05. These findings suggest that the THINQING learning medium—particularly its error-based explanatory feedback mechanism—is effective in supporting the development of computational thinking and can serve as an alternative interactive learning tool for fostering 21st-century skills in secondary education.